The Thermal Activity of Normal and Malignant Tissues. Issue 2 (1998) - Mack, Peter; Cheng, Li-Yao
Abstract : The usefulness of metabolic heat measurements in quantifying the response of a solid tumour to anticancer treatment was evaluated. The heat production characteristic of malignant tissues, as measured from human stomach, breast and liver cancer samples, was observed to be inconsistent, and its value could be higher or lower than that of its normal tissue of origin. The various thermal activity responses of an experimental rat hepatoma to hepatic artery ligation, cryotherapy, intra-arterial (i.a) Adriamycin (2.4 mg/ kg), i.a. Norcantharidin (0.5 mg/kg) were next studied. The tumour/liver (T/L) ratio of untreated tumour-bearing rats was 0.83 but this fell to a minimum at 24 h in both the hepatic artery ligation and the cryosurgery groups. In these two groups marked fluctuations in the heat production of normal liver occurred with poor recovery of the T/ L ratio even at 2--3 weeks. In the Adriamycin group, the T/L ratio dropped to a minimum at 5 days, and in the Norcantharidin group, at 3 days. Minimal disturbances in the thermal activity of liver tissue occured in these two chemotherapy groups and the T/L ratio recovered by 3 weeks. Norcantharidin appeared as efficacious as Adriamycin in the treatment of hepatoma when evaluated in terms of thermal activity.